PROSES STERILISASI SARI BUAH TERONG UNGU (Solanum melongena) DENGAN SISTEM OZONISASI - Suharyono A. S.; Udin Hasanudin; M. Kurniadi (Research Center for Chemistry - LIPI, 2011)
One effort in the preservation of food is processed through a sterilization process using ozonization system with ozone molecule (0). The purpose of this study is to review the process of sterilization of juice eggplant (Solanum melongena) using ozonation systems with a concentration of 0.6 ppm ozone. In this study, eggplant juice made in 6 ratio of water: sugar(1:10%, 1:15%, 1:20%, 2:10%, 2:15%, 2:20%) and sterilize with 0.6 ppm ozone The ozonation time studiedfor (0. 6ppm) 0 min, 2 min, 4 minutes, 6 minutes, 8 min and long storage 0 days, 2 days, 4 days, 6 day. Test parameters obtained included the juice organoleptic test (preference level) and test of vitamin C. The results showed that ozonation can be used as a process of sterilization of juice eggplant, ozonation time with optimal and durable power offruit quality is 4minutes with long storage for 2 days. Response panelists on organoleptic test as a whole eggplant juice between 2.8 (preferred), and 3.13 (preferred). Levels of vitam in C, protein, carbohydrate and total microbial best eggplant juice are 1.35 mg1100mL, 1.1%, 3.43 mg1100mL, 8.36x1 rI cfulmL, respectively.Key words: Eggplant, ozonization, ozone,sterilization.